Characterization of phenazine and phenazine-1-carboxylic acid isolated from Pseudomonas aeruginosa UPMP3 and their antifungal activities against Ganoderma boninense - Lee, Kai Wei; Omar, Dzolkhifli; Ee, Gwendoline Cheng Lian; Nasehi, Abbas; Wong, Mui Yun (Universiti Putra Malaysia Press, 2018)
The structural characterization of two phenazines, produced simultaneously through biosynthesis by Pseudomonas aeruginosa UPMP3 were studied. The phenazine antibiotics play an important role in antimicrobial activities and potentially could be used in biopesticide formulation to control basal stem rot of oil palm. The antibiotics were identified through high-performance liquid chromatography (HPLC) and confirmed using Fourier Transform Infrared (FTIR) spectroscopy. The specific representations in the FTIR spectra of the purified compounds such as absorption peaks at 1353.68 (aromatic nitro compound), 1118.84 and 729.43 cm-1 (aromatic ring) were indications of phenazine (PHZ) whereas, absorption peaks at 1717.92 (carboxylic acid), 861.78 and 738.54 cm-1 (aromatic ring) were indicatives of phenazine-1-carboxylic acid (PCA). The structures of the compounds were further confirmed by 1H NMR/13C NMR spectroscopy as PHZ (C12H8N2) and PCA (C13H8N2O2). Ganoderma boninense was sensitive to purified phenazine antibiotics especially phenazine and a concentration of 1000 ppm completely inhibited the mycelial growth. As far as we know, this is the first study where purified phenazine antibiotics isolated from P. aeruginosa UPMP3 were structurally characterised and tested to have positive antagonism against G. boninense.